Alterações funcionais e morfológicas do músculo quadríceps induzidas pelo treinamento excêntrico após reconstrução do LCA - Brasileiro, Jamilsom Simões (2004)
The anterior cruciate ligament (ACL) is the most commonly injured ligament in the knee and its rupture results in pain, instability, muscle atrophy and weakness. The quadriceps femoris muscle dysfunction is common before and after ACL reconstruction and can persist over years. A detailed understanding of neuromuscular function after ACL reconstruction is critical to the development of optimal rehabilitation strategies. The purpose of this study was to investigate the contributions of functional and morphological factors, in the muscle recovery, after ACL reconstruction. The effects of two therapeutic methods, usually utilized to recover muscle strength were also evaluated: Neuromuscular Electrical Stimulation (NMES) and eccentric exercise. Eight subjects (age = 31.3 ± 5.8 years) who had undergone ACL ligament reconstruction (mean 9.4 ± 0.7 months after the surgery) were randomly assigned to either an eccentric exercise associated with NMES (russian current) or only an eccentric exercise group. Only the involved limb was trained 2 days a week, for 12 weeks. The uninvolved one was also evaluated as reference. The quadriceps muscle function was evaluated by the measurement of the knee extensor torque during isometric and eccentric isokinetic contractions (30 and 120º/s) and by surface electromyography (EMG) of the Vastus Medialis Obliquos (VMO), Vastus Lateralis (VL) and Rectus Femoris (RF) muscles. The quadriceps cross-sectional area (CSA) was measured in six regions using Nuclear Magnetic Resonance Imaging (MRI-I). The initial evaluation showed significant extensor torque deficit both in isometric and eccentric conditions of the involved limb, compared to the contralateral one. There was significant muscle atrophy along the quadriceps extension, mainly in the distal thigh region. The EMG activity was lower for the VMO in all tested situations. NMES did not interfere in the gain of muscular strength, in any of the evaluated functions. The eccentric training increased significantly the isometric (from 198 ± 37 to 228 ± 48 Nm, p<0.05) and eccentric torque at 30 and 120º/s (from 227 ± 56 to 291 ± 65, p< 0.01 and from 199 ± 51 to 240 ± 63, p< 0.05, respectively). Quadriceps cross-sectional area also increased at all the evaluated regions for the involved limb, and the highest hypertrophy was at the thigh proximal region (from 169 ± 27 to 189 ± 25,8 cm2, p< 0.01 ), when compared to the distal region (form 31,5 ± 5,9 to 35,1 ± 6,1 cm2, p< 0.01). The EMG activity of VMO was recovered after the first six weeks of eccentric training. In the same period, the increased extensor torque showed correlation with the increased quadriceps cross-sectional area (r=0,81) and with the recovery of motor unit activation (r=0.69). After twelve weeks of training, there was correlation only between increased torque and cross-sectional area (r=0.78). In conclusion: 1) eccentric training showed to be a potent resource in the recovery of both morphological and functional factors of quadriceps, after ACL reconstruction; 2) NEMS did not interfere in the rehabilitation of these individuals.